Implementation of Information Technology Through the Development of the Jatipancur Village Profile Website as an Effort to Digitize Public Information - Arhamzah, Andi Muhammad Ilham; Fitriyanto, A Alvian; Kusumah, Billi Rifa; Fauzi, Fais Indra; Amal, Muhammad Ikhlasul; Sopianto, Sopianto (Jurnal Pengabdian Kepada Masyarakat Untukmu Nusantara, 2026)
Digital transformation at the village government level is urgently needed to support information transparency and public services. Through the Community Service Program (KKN), students of Universitas Nahdlatul Ulama Cirebon developed the Jatipancur Village profile website, Greged District, Cirebon Regency. The aim was to provide an open, systematic, and easily accessible information medium for the community. The method included observation, interviews, information needs analysis, WordPress-based design, implementation, and training for village officials. The results show that the website of Jatipancur Village presents demographic data (4,769 residents, 1,352 households, 3,213 voters, 159 elderly, 81 orphans, 36 people with disabilities, and education dominated by elementary school graduates), village institutions, facilities, and news such as village anniversary celebrations and KKN programs. The website improves transparency and serves as an open database for development planning. Thus, village information digitalization through website development is proven effective as a strategy for community empowerment and as a replicable model for other villages.